Comprehensive energy management : eco routing & velocity profiles - Watzenig, Daniel; Brandstätter, Bernhard (SpringerBriefs in applied sciences and technology. Automotive engineering: simulation and validation methods., 2017)
The book discusses the emerging topic of comprehensive energy management in electric vehicles from the viewpoint of academia and from the industrial perspective. It provides a seamless coverage of all relevant systems and control algorithms for comprehensive energy management, their integration on a multi-core system and their reliability assurance (validation and test). Relevant European projects contributing to the evolvement of comprehensive energy management in fully electric vehicles are also included.